Effect of age on in vivo rates of mitochondrial protein synthesis in human skeletal muscle - Rooyackers, Olav E. (The National Academy of Sciences of the USA, 1996)
A progressive decline in muscle performance in the rapidly expanding aging population is causing a dramatic increase in disability and health care costs. A decrease in muscle endurance capacity due to mitochondrial decay likely contributes to this decline in muscle performance. We developed a novel stable isotope technique to measure in vivo rates of mitochondrial protein synthesis in human skeletal muscle using needle biopsy samples and applied this technique to elucidate a potential mechanism for the age-related decline in the mitochondrial content and function of skeletal muscle. The fractional rate of muscle mitochondrial protein synthesis in young humans (24 ± 1 year) was 0.081 ± 0.004%·h(−1), and this rate declined to 0.047 ± 0.005%·h(−1) by middle age (54 ± 1 year; P < 0.01). No further decline in the rate of mitochondrial protein synthesis (0.051 ± 0.004%·h(−1)) occurred with advancing age (73 ± 2 years). The mitochondrial synthesis rate was about 95% higher than that of mixed protein in the young, whereas it was approximately 35% higher in the middle-aged and elderly subjects. In addition, decreasing activities of mitochondrial enzymes were observed in muscle homogenates (cytochrome c oxidase and citrate synthase) and in isolated mitochondria (citrate synthase) with increasing age, indicating declines in muscle oxidative capacity and mitochondrial function, respectively. The decrease in the rates of mitochondrial protein synthesis is likely to be responsible for this decline in muscle oxidative capacity and mitochondrial function. These changes in muscle mitochondrial protein metabolism may contribute to the age-related decline in aerobic capacity and muscle performance.